Islamic Counseling with Sholawat in Overcoming the Emotional Challenges of Children with Autism - Alamin, Muhammad Nafi’ Lil; Muhammadah, Sunnatul (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study explores the role of sholawat practices in overcoming emotional challenges in autistic children, focusing on the views of teachers at the Muhammadiyah Sidayu Gresik Special School (SLB). Using a qualitative approach, data were collected through in-depth interviews with teachers who have experience integrating sholawat in the learning process. The focus of the study was on teachers’ observations of the impact of sholawat on the emotional and behavioral conditions of autistic students. The results showed that the integration of sholawat, both through listening and chanting, was indicated to contribute to positive changes in a student, including increased focus, response to interactions, and engagement in daily activities. Teachers’ perspectives highlighted the potential of sholawat as a calming and attention-directing intervention. In addition to sholawat, students’ interest in other music and religious activities were also observed to have a positive influence. This study concludes that sholawat has the potential to be one of the effective local wisdom-based approaches in supporting the management of emotional challenges in autistic children, by emphasizing the importance of holistic interventions that consider spiritual aspects and individual preferences.